Probing protein structure and dynamics through native MS and H/D exchange - Chandler, S (2019)
This thesis details the development and application of mass spectrometry (MS) labelling strategies for use in structural biology, and, specifically, how they offer insight into the quaternary structure and dynamics of protein complexes. Chapter 3 first demonstrates the utility of isotopic H/D exchange (HDX) strategies for probing the in solution dynamics and assembly of two protein systems. Firstly, I use solution HDX to probe the light-induced structural change of the FAD-binding protein cryptochrome. Through quantitative analysis, I discover a region at the C-terminus undergoes a long-lived conformational change with high specificity to blue light, suggesting a potential role in the signalling cascade of circadian processes. Secondly, I use HDX-MS to probe the interface of a homo-dimeric ancestor of extant haemoglobin. Differential HDX-MS revealed protected peptide regions consistent with the alpha/beta packing interface in the modernday hetero-tetramer. Studying proteins in the gas-phase by using native MS has the distinct advantage of high resolution separations, manipulations and accurate mass determination, afforded by the exquisite control possible in vacuum. Chapters 4, 5 and 6 describe the implementation of performing gas-phase HDX (gpHDX) inside the spectrometer and how the technique may be used to interrogate protein ion structure with high specificity. I first demonstrate how gpHDX can be used to probe native proteins and show high sensitivity to the surface chemistry of exposed residues. Secondly, I use gpHDX to aid our understanding of how protein complexes asymmetrically dissociate through collisional activation and charge precipitated unfolding. Importantly, I show that the deuterium uptake of a dissociated subunit can be used as a proxy for the intact precursor. Finally I use gpHDX coupled to ion mobility (IM) to reveal how the conformational landscape of an activated protein changes at a global and local level.